Challenges encountered in conducting donor‐based research: Lessons learned from the Donor Heart Study. Issue 7 (18th April 2022) - Khush, Kiran K.; Luikart, Helen; Neidlinger, Nikole; Salehi, Ahmad; Nguyen, John; Geraghty, P. J.; Belcher, John; Nicely, Bruce; Jendrisak, Martin; Pearson, Thomas; Wood, R. Patrick; Groat, Tahnee; et al.
Abstract : Solid organ transplantation continues to be constrained by a lack of suitable donor organs. Advances in donor management and evaluation are needed to address this shortage, but the performance of research studies in deceased donors is fraught with challenges. Here we discuss several of the major obstacles we faced in the conduct of the Donor Heart Study—a prospective, multi‐site, observational study of donor management, evaluation, and acceptance for heart transplantation. These included recruitment and engagement of participating organ procurement organizations, ambiguities related to study oversight, obtaining authorization for donor research, logistical challenges encountered during donor management, sustaining study momentum, and challenges related to study data management. By highlighting these obstacles encountered, as well as the solutions implemented, we hope to stimulate further discussion and actions that will facilitate the design and execution of future donor research studies. Abstract : The authors reflect on the challenges encountered and lessons learned in conducting the Donor Heart Study, a recently‐completed multicenter, prospective, observational study that aims to develop evidence‐based criteria for donor heart evaluation and acceptance for transplantation.